Can We Boost Preschoolers' Inhibitory Performance Just by Changing the Way They Respond?. Issue 6 (2nd July 2021) - Carroll, Daniel J.; Blakey, Emma; Simpson, Andrew
Abstract : Changing the way children make their response appears to sometimes, but not always, boost their inhibitory control—though interpreting existing findings is hampered by inconsistent methods and results. This study investigated the effects of delaying, and changing, the means of responding. Ninety‐six preschoolers ( M age 46 months) completed tasks assessing inhibitory control, counterfactual reasoning, strategic reasoning, and false belief understanding. Children responded either immediately or after a delay, and either by pointing with their finger, or with a hand‐held arrow. Delaying boosted performance on all tasks except false belief understanding; arrow‐pointing only improved strategic reasoning. It is suggested that delay helps children work out the correct response; it is unlikely to help on tasks where this requirement is absent.